Shedding of Syndecan-1/CXCL1 Complexes by Matrix Metalloproteinase 7 Functions as an Epithelial Checkpoint of Neutrophil Activation - Gill, Sean E. (Am J Respir Cell Mol Biol, 2016)
Although neutrophils play critical roles in innate immunity, in excess these cells cause severe tissue damage. Thus, neutrophil activation must be tightly regulated to prevent indiscriminant damage. Previously, we reported that mice lacking matrix metalloproteinase (MMP) 7 are protected from lung injury owing to markedly impaired neutrophil movement from the interstitium into mucosal lumenal spaces. This phenotype resulted from a lack of MMP7 shedding of syndecan-1, a heparan sulfate proteoglycan that carries the neutrophil chemokine CXCL1 as cargo. Here, we assessed if shedding syndecan-1/CXCL1 complexes affects neutrophil activation. Whereas injured monolayers of wild-type alveolar type II cells potently stimulated neutrophil activation, as gauged by release of myeloperoxidase, cells from Mmp7(−/−) or syndecan-1-null (Sdc1(−/−)) mice or human cells with MMP7 knockdown did not. In vivo, we observed reduced myeloperoxidase release relative to neutrophil numbers in bleomycin-injured Mmp7(−/−) and Sdc1(−/−) mice. Furthermore, we determined that soluble syndecan-1 directly stimulated neutrophil activation in the absence of cellular damage. These data indicate that MMP7 shedding of syndecan-1/CXCL1 complexes functions as a checkpoint that restricts neutrophil activation at sites of epithelial injury.